The Examination of Self-Efficacy Beliefs of Physical Education Pre-Service Teachers According to Different Variables - Ayşe Feray Özbal; Tolga Eski; Arıkan Ektirici (Türk Spor ve Egzersiz Dergisi)
Education is becoming more and more important in today’s world. It is also acknowledged that training teachers with high levels of self-confidence in education faculties is likely to improve the quality of education in the future. Bandura (3) proposed the term “self-efficacy” for the first time in 1977 in his book titled Self-efficacy: Toward a Unifying Theory of Behavioral Change. He based this concept on Social Learning Theory and defined it as “ one’s belief about his/her own ability to acquire a specific behavior successfully”. It has been witnessed that self-efficacy beliefs of pre-service teachers affect their perception about students, behaviors, eagerness to learn, experiences and learning outcomes. Thus, this study aims to determine self-efficacy beliefs of pre-service teachers of physical education and sports regarding teaching profession and to examine whether the data obtained vary according to certain variables. The study used survey method. A total of 526 university students (222 female and 304 male) who attend the Physical Education and Sports Teaching Departments of 6 different universities in Turkey participated in the study on a voluntary basis. Developed by the researchers, this form includes questions aiming to obtain the following information about the participants: age, gender, the university they attend, class level, family income level, and educational background of parents. In addition, the study used “Teacher Self-efficacy Scale”, which was developed by Tschannen-Moran and Woolfolk Hoy (21) and adapted to Turkish context by Çapa et al. (7). The data was analyzed by using SPSS 22 software and descriptive analysis, independent variable t-test and ANOVA tests were used.    There was a meaningful difference in ‘’Student Participation’’ and ‘’Classroom Management’’ sub-dimensions in terms of university variable (p lt;05). Likewise, there was a meaningful difference in ‘’Student Participation’’ and ‘’Classroom Management’’ sub-dimensions in terms of mother’s educational background variable (p lt;05). As a result, meaningful differences were found in variables such as university and mother’s educational background. The reason may be that universities took place in different geographical areas of the country. It can be said that the effect of the level of education of the mother on the growth environment is the reason for this difference.